Chemically imaging nanostructures formed by the covalent assembly of molecular building blocks on a surface with ultrahigh vacuum tip-enhanced Raman spectroscopy. (18th May 2022) - Schultz, Jeremy F; Li, Linfei; Mahapatra, Sayantan; Jiang, Nan
Abstract: Surface-bound reactions have become a viable method to develop nanoarchitectures through bottom-up assembly with near atomic precision. However, the bottom-up fabrication of nanostructures on surfaces requires careful consideration of the intrinsic properties of the precursors and substrate as well as the complex interplay of any interactions that arise in the heterogeneous two-dimensional (2D) system. Therefore, it becomes necessary to consider these systems with characterization methods sensitive to such properties with suitable spatial resolution. Here, low temperature ultrahigh vacuum scanning tunneling microscopy (STM) and tip-enhanced Raman spectroscopy (TERS) were used to investigate the formation of 2D covalent networks via coupling reactions of tetra(4-bromophenyl)porphyrin (Br4 TPP) molecules on a Ag(100) substrate. Through the combination of STM topographic imaging and TERS vibrational fingerprints, the conformation of molecular precursors on the substrate was understood. Following the thermally activated coupling reaction, STM and TERS imaging confirm the covalent nature of the 2D networks and suggest that the apparent disorder arises from molecular flexibility.